ZAKAT MADU: Studi Pemikiran Mazhab Hanafiyah dan Mazhab Syafi’iyah - niah, qusthoniah qusthoniah; Rudialis, Rudialis (Syari'ah, 2021)
Zakat is obligatory for someone who has fulfilled the mandatory zakat requirements for both the owner and his property. Zakat aims to increase the benefit of the people and be able to improve the economic life and welfare of the people. One of the things that must be zakat is honey, both bee honey which is obtained directly from the hive and bee honey from beekeeping products. Livestock honey is divided into two, some are grazed and some are not. According to the Hanafi school of honey, zakat must be issued and the amount of zakat is 10%. However, this provision does not apply if the bee is nesting in the Kharajiyah land, because the Kharajiyah land has been taxed. The Shafi'iyah school has two opinions regarding honey zakat. In its qaul qadim, it is stated that honey must be paid zakat. Meanwhile, in qaul Jadid, he argues that zakat is not obligatory to be issued because honey is not a staple food and does not have strong arguments, both Sunnah and Atsar. The things that underlie differences of opinion regarding zakat honey are different understandings of the hadiths and the validity of the hadith regarding zakat honey, the use of different qiyas, and the use of different Qaul Sohabiy (opinions of friends). KEYWORDS: Honey Zakat, the Mazhab Hanafiyah and the Mazhab Syafi'iyah